Mandarin Language Strengthens Tolerance and Patriotism in a Multiracial Society - Yong, Ying Mei (2018)
Kuantan, 21 September 2018- Ms. Yong Ying Mei, the Director of Mandarin Language and Culture Centre (MLCC) of Universiti Malaysia Pahang (UMP) was invited as one of the panels for the Cendekia Bicara forum during the closing ceremony for Festival ‘Aku Darah Anak Malaysia A.D.A.M’ at Universiti Malaysia Pahang (UMP). In the forum, she emphasized that the language is a part of Malaysian identity who are able to speak several languages. She also mentioned that Mandarin language strengthens tolerance and patriotism in a multiracial society.